2020
DOI: 10.1097/aln.0000000000003628
|View full text |Cite
|
Sign up to set email alerts
|

An Electroencephalogram Metric of Temporal Complexity Tracks Psychometric Impairment Caused by Low-dose Nitrous Oxide

Abstract: Background Nitrous oxide produces non–γ-aminobutyric acid sedation and psychometric impairment and can be used as scientific model for understanding mechanisms of progressive cognitive disturbances. Temporal complexity of the electroencephalogram may be a sensitive indicator of these effects. This study measured psychometric performance and the temporal complexity of the electroencephalogram in participants breathing low-dose nitrous oxide. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Our study found a non‐dose‐dependent decrease in DMN temporal complexity, which was similar in magnitude to the reduction caused by 30% end‐tidal nitrous oxide (Vrijdag et al, 2021). Nitrous oxide is known to increase the excitability of the brain (Hirota, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study found a non‐dose‐dependent decrease in DMN temporal complexity, which was similar in magnitude to the reduction caused by 30% end‐tidal nitrous oxide (Vrijdag et al, 2021). Nitrous oxide is known to increase the excitability of the brain (Hirota, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…The study protocol was approved by the Health and Disability Ethics Committee, Auckland, New Zealand (reference 16/NTA/93), and was registered with the Australian New Zealand Clinical Trial Registry (ANZCTR: U1111‐1181‐9722, http://www.anzctr.org.au/, RRID:SCR_002967). The sample size was based on similar studies previously published (Biersner et al, 1977; Fowler et al, 1983; Hamilton et al, 1992; Vrijdag et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The next 50 minutes of nitrous oxide exposure (sedation) were marked by periodically quiescent behavior, gradual decline in prefrontal and parietal acetylcholine levels, and global suppression of EEG complexity that was most pronounced in frontal channel clusters. The topographic distribution of changes in EEG complexity during subanesthetic ketamine and nitrous oxide sedation in our study broadly mirrored recent magnetoencephalographic and EEG data published during ketamine and nitrous oxide administration in humans, 12 , 28 suggesting a comparable dynamic landscape during the administration of dissociative anesthetics in rodents.…”
Section: Discussionsupporting
confidence: 87%
“…The remaining epochs for that condition and exposure were stored for further analysis. See Vrijdag et al (2021) for the script 57 .…”
Section: Methodsmentioning
confidence: 99%